Photothermal conversion of Bi2Se3 nanosheets and efficient steam generation by capillary siphoning - Yanling Liu; Yanbang Zhang; Guozhi Jia (Energy Reports, 2020)
Local heating under light illumination provides a noncontact way to present an enormous superiority for minimum heat dissipation compared with other cases, such as floating on the surface of water. The highly-effective broadband absorption of Bi2Se3 covering both infrared and visible wavelength range can result in a high efficiency of 68% at 1 W/cm2 light illumination. The device possesses the barrier-free path to ensure the generated steam fast escape from the water surface also achieves the local heat generation and straightway wicks the adequate micro-flow to hot zone. The highlighted advantage of our design is that the efficiency is scarcely susceptible even the uninterrupted water flow, unlike the floated film, the heat dissipation is bound to generate due to the heat exchange between the heated and unheated water. The trade-off between temperature and water supplement should be ensured under the large heat generation and maintain an ideal evaporation rate for solar desalinate application.
Keywords: 330